2021
DOI: 10.1002/adma.202103620
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Wettability in Pristine Graphene

Abstract: The wettability of graphene remains controversial owing to its high sensitivity to the surroundings, which is reflected by the wide range of reported water contact angle (WCA). Specifically, the surface contamination and underlying substrate would strongly alter the intrinsic wettability of graphene. Here, the intrinsic wettability of graphene is investigated by measuring WCA on suspended, superclean graphene membrane using environmental scanning electron microscope. An extremely low WCA with an average value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…XPS analysis results showed that a large amount of C=C remained on the substrate surfaces, and only PMMA contained C=C during the experiment. Compared with the water contact angle test and XPS results (Figures 6-9), it was found that the less the PMMA contamination, the smaller the water contact angle, consistent with the reported work [35,36]. Additionally, PMMA can cause p-type doping with graphene [20,21], leading to a competitive relationship with H2O and doped graphene, in turn resulting in a smaller binding force and larger contact angle.…”
Section: Element and Composition Measurement By Xpssupporting
confidence: 85%
“…XPS analysis results showed that a large amount of C=C remained on the substrate surfaces, and only PMMA contained C=C during the experiment. Compared with the water contact angle test and XPS results (Figures 6-9), it was found that the less the PMMA contamination, the smaller the water contact angle, consistent with the reported work [35,36]. Additionally, PMMA can cause p-type doping with graphene [20,21], leading to a competitive relationship with H2O and doped graphene, in turn resulting in a smaller binding force and larger contact angle.…”
Section: Element and Composition Measurement By Xpssupporting
confidence: 85%
“…The atomic force microscopy (AFM) image further confirmed the successful preparation of large, single-layer MXene with a uniform thickness of 1.7 nm (Figure c). Since the abundant pores and hydrophilicity derived from the hydrophilic functional groups formed in the preparation process of SA-CNT films (Figure S3), the MXene flakes could be infiltrated into the SA-CNT films and adhered well to SA-CNT skeleton (Figure S4a,b). A further chemical-cross-linking significantly improved the mechanical strength of the MXene/SA-CNT films due to the formation of strong covalent interactions between MXene layers.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, we prepared graphene nanocapsules with hole diameters of 300 and 600 nm and experimentally measured their thicknesses (21 nanocapsules for each diameter) from their tilted SEM images. 42,43 Under the typical vacuum condition of SEM (∼10 −10 MPa), the shapes of our graphene nanocapsules are close to a combination of two different halfellipses as a result of the projection of perfect spherical nanocapsules (Figure 5c,d); therefore, the half thickness (h) of the nanocapsule can be obtained by eq 2 43…”
mentioning
confidence: 84%
“…The calculated thickness profiles for liquid capsules in Figure a,b show that the capsules become thicker as their radius increases and/or the pressure difference increases. Indeed, we prepared graphene nanocapsules with hole diameters of 300 and 600 nm and experimentally measured their thicknesses (21 nanocapsules for each diameter) from their tilted SEM images. , Under the typical vacuum condition of SEM (∼10 –10 MPa), the shapes of our graphene nanocapsules are close to a combination of two different half-ellipses as a result of the projection of perfect spherical nanocapsules (Figure c,d); therefore, the half thickness ( h ) of the nanocapsule can be obtained by eq where r is the radius of the graphene nanocapsule, θ is the contact angle, which can be expressed by eq where T is the tilt angle for SEM imaging (we used 56°) and the geometrical lengths a , b , and r ( b is used only for the validation of eq : a > b ) in Figure d were measured using image-processing software (ImageJ). The statistical results in Figure e show that the average thickness of a graphene nanocapsule increases as the diameter of the nanohole increases (150 ± 3 and 256 ± 2 nm for nanocapsules with hole diameters of 300 and 600 nm, respectively).…”
mentioning
confidence: 99%